Same-Sex Friendship, School Gender Composition, and Substance Use: A Social Network Study of 50 European Schools. (12th May 2018) - Grard, Adeline; Kunst, Anton; Kuipers, Mirte; Richter, Matthias; Rimpela, Arja; Federico, Bruno; Lorant, Vincent
ABSTRACT: Background : Other-sex friendship (girls with boy friends, boys with girl friends) has been associated with substance use, but how the gender composition of schools influences substance use has not been known. Objectives : We analyzed the influence of other-sex friendship on substance use and took into account the proportion of each gender group at the schools, and hypothesized that other-sex friendship is associated with higher levels of substance use and that schools with a majority of males have higher levels of use than female-majority schools. Methods : In 2013, a social network survey was carried out in six European cities. In each city, schools were selected and 11, 015 adolescents (aged 14-16) were recruited (participation rate = 79.4%). We collected data on smoking, binge drinking, cannabis use, and peer group composition. Results : Other-sex friendship was associated with smoking, binge drinking, and cannabis use for girls and with smoking for boys. Substance use was more frequent in schools with a majority of males. Conclusions/Importance : Adolescent girls are best protected from substance use if they are in gender-balanced schools, but in same-sex friendship. This offers new perspectives on gender mixing at school. In schools with a majority of boys, more attention should be paid to girls, and gender-specific health promotion programs should be implemented. This European study is the first to take into account both individual (other-sex friendship) and contextual (gender composition of schools) gender interactions. It confirms previous studies on other-sex friendship, while shedding light on the influence of gender-normative contexts on substance use.